1975
DOI: 10.1017/s0373463300037668
|View full text |Cite
|
Sign up to set email alerts
|

The Tercentenary of The Royal Observatory at Greenwich

Abstract: According to Flamsteed's own account, the Royal Observatory was founded as a direct consequence of the representation in 1674 by a Frenchman, who described himself as Le Sieur de St. Pierre, to the English Court that he had discovered a method of determining longitude at sea ‘from easy celestial observations’, and claimed the appropriate award. The solution to the ‘longitude problem’ was then, as it had been for many years and was to be for a further 90 years, of paramount importance; several countries had off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…However, the main feature is the decrease of the southerly flux within 6" of latitude, indicating convergence of moisture flux. The large value of precipitation in box 3 fits well with the climatological position of the line of maximum cloudiness for May (Sadler 1975). In the continental boxes the meridional flux is from the north and decreases as the air moves south towards the zone of convergence.…”
Section: (A) Water Vapour Budgetssupporting
confidence: 68%
“…However, the main feature is the decrease of the southerly flux within 6" of latitude, indicating convergence of moisture flux. The large value of precipitation in box 3 fits well with the climatological position of the line of maximum cloudiness for May (Sadler 1975). In the continental boxes the meridional flux is from the north and decreases as the air moves south towards the zone of convergence.…”
Section: (A) Water Vapour Budgetssupporting
confidence: 68%
“…The supernova remnants (SNR) in the Large Magellanic Cloud (LMC), which have recently been discussed by Mathewson and Clarke (1973), Danziger and Dennefeld (1976ö), and Lasker (1976), are obvious candidates for more detailed observations by direct imaging because they lie in relatively uncluttered and unobscured areas at a known and common distance. Accordingly, in 1975 we began a photographic survey for the purpose of comparing the nebular structure in a high-excitation line with that in a low-excitation one.…”
mentioning
confidence: 99%
“…Previous experience with SNRs in the LMC (Lasker 1976) showed that the appearances in Ha + [N n] and in [S n] ÂÀ6716, 6731 are quite similar, and the [S n] was chosen over the Ha because it is less influenced by confusion from nearby (radiatively energized) nebulae and because it is more easily excited. (Also, instrumental limitations precluded our separating Ha and [N ii] ÂÀ6548, 6583.)…”
mentioning
confidence: 99%
“…2 The development a century later of the chronometer by John Harrisonp rovided the first portable gauge for use by the mariner and enabled a complete scientific basis to be established for navigation at. sea.…”
mentioning
confidence: 99%
“…The establishment in 167^ of the Royal Greenwich Observatory was the direct consequence of the need to provide such a laboratory gauge. 2 The development a century later of the chronometer by John Harrisonp rovided the first portable gauge for use by the mariner and enabled a complete scientific basis to be established for navigation at. sea.…”
mentioning
confidence: 99%